Identification and characterization of a novel triyne and cinnamate 4-hydroxylase in Helichrysum aureonitens Sch. Bip. - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2009.